Understanding the meaning of youth sexual and reproductive well-being in Fiji. Issue 11 (2nd November 2018) - O'Connor, Michelle; Rawstorne, Patrick; Devi, Rachel; Iniakwala, Dennie; Razee, Husna
Abstract: Well-being is a term commonly used in discussions of sexuality, reproduction and sexual health, yet the meaning of the term is elusive and often disregarded. As an example, the 'well-being' component of sexual and reproductive health and well-being is often not explicitly addressed in research, policy and programme development. The goal of this paper is to explore the meanings of sexual and reproductive well-being among young people in Fiji and their implications. Fourteen focus group discussions with young people aged 15 to 19 years and 40 key informant interviews were held in four Fijian settings. We found both different and shared meanings of sexual and reproductive well-being and suggest areas in which it can be strengthened in Fiji.